2000
DOI: 10.1111/j.1751-0813.2000.tb10444.x
|View full text |Cite
|
Sign up to set email alerts
|

Mastitis, polyarthritis and abortion caused by Mycoplasma species bovine group 7 in dairy cattle

Abstract: Mycoplasma sp bovine group 7 caused significant economic losses as a result of polyarthritis, abortion and mastitis. The disease probably originated from udder infections with spread being facilitated by the decreased use of tetracycline in the treatment of mastitis. Neonatal calves were most likely infected by the consumption of milk contaminated with the organism. Abortions presumably resulted from mycoplasmaemia. This appears to be the first report in Australia of bovine abortion resulting from Mycoplasma s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 15 publications
2
47
0
1
Order By: Relevance
“…Although the role of H 2 O 2 in the pathogenesis of Mycoplasma sp. bovine group 7 infections is unclear, field strains isolated during a recent outbreak of polyarthritis, mastitis and abortion were able to haemolyse red blood cells when cultured on sheep blood agar (Hum et al, 2000). These observations suggest that the release of H 2 O 2 by Mycoplasma sp.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Although the role of H 2 O 2 in the pathogenesis of Mycoplasma sp. bovine group 7 infections is unclear, field strains isolated during a recent outbreak of polyarthritis, mastitis and abortion were able to haemolyse red blood cells when cultured on sheep blood agar (Hum et al, 2000). These observations suggest that the release of H 2 O 2 by Mycoplasma sp.…”
Section: Discussionmentioning
confidence: 63%
“…Twenty-four isolates of Mycoplasma sp. bovine group 7 were recovered from multiple joint fluids, pericardial fluid and a lymph node of affected calves, from individual and bulk milk samples, and from the internal organs (liver, spleen, lung and stomach contents) of two aborted foetuses (Hum et al, 2000). Fingerprinting studies showed that all 24 isolates were indistinguishable from one another but could be readily differentiated from a collection of epidemiologically unrelated Australian and international isolates of this species (Djordjevic et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…MmmSC is responsible for contagious bovine pleuropneumonia (CBPP), which is considered to be the most important threat to cattle farming in affected countries, and one which impacts farmers directly through mortality and poor productivity of their animals. M. leachii is associated with polyarthritis in calves (12,23,24) and with mastitis (6), pneumonia (2), and abortion (12) in cows. Whereas, three M. mycoides cluster members, Mccp, Mmc, and Mcc, are the caprine pathogens.…”
Section: Introductionmentioning
confidence: 99%